Importance of adhesins in virulence of Paracoccidioides spp. - Oliveira, Haroldo C. de [UNESP] (2015)
Members of the Paracoccidioides genus are the etiologic agents of paracoccidioidomycosis (PCM). This genus is composed of two species: Paracoccidioides brasiliensis and Paracoccidioides lutzii. The correct molecular taxonomic classification of these fungi has created new opportunities for studying and understanding their relationships with their hosts. Paracoccidioides spp. have features that permit their growth under adverse conditions, enable them to adhere to and invade host tissues and may contribute to disease development. Cell wall proteins called adhesins facilitate adhesion and are capable of mediating fungi-host interactions during infection. This study aimed to evaluate the adhesion profile of two species of the genus Paracoccidioides, to analyze the expression of adhesin-encoding genes by real-time PCR and to relate these results to the virulence of the species, as assessed using a survival curve in mice and in Galleria mellonella after blocking the adhesins. A high level of heterogeneity was observed in adhesion and adhesin expression, showing that the 14-3-3 and enolase molecules are the most highly expressed adhesins during pathogen-host interaction. Additionally, a survival curve revealed a correlation between the adhesion rate and survival, with P. brasiliensis showing higher adhesion and adhesin expression levels and greater virulence when compared with P. lutzii. After blocking 14-3-3 and enolase adhesins, we observed modifications in the virulence of these two species, revealing the importance of these molecules during the pathogenesis of members of the Paracoccidioides genus. These results revealed new insights into the host-pathogen interaction of this genus and may enhance our understanding of different isolates that could be useful for the treatment of this mycosis.